EVALUATION OF BACKGROUND RADIATION IN RESIDENTIAL AREAS NEAR IIUM KUANTAN CAMPUS - SOHAIMI, NORHANNA; KHAIRUSALLEH, KASHFI; JUNET, LAILA KALIDAH (International Journal of Allied Health Sciences, 2021)
Introduction: The purpose of this study is to monitor the amount of background radiation at residential areas near IIUM Kuantan Campus using optically stimulated luminescene dosimeter (OSLD). Methods: A total of 28 OSLDs were used in this study. The OSLDs were placed in seven residential areas near IIUM Kuantan Campus which were Indera Mahkota 2 (IM2), Indera Mahkota 6 (IM6), Indera Mahkota 8 (IM8), Indera Mahkota 15 (IM15), Astana Permai, Bukit Istana and KotaSAS with the duration of 18 days. Four OSLDs were placed at each residential area, three OSLDs were placed for 48 hours (2 days) whereas the remaining OSLD was left at the designated location until the 18th day as a control OSLD. microStar reader was used to read the OSLD and the results were analyzed using Microsoft (MS) Excel. Results: Generally, all seven residential areas near IIUM Kuantan Campus showed a steady increasing pattern of background radiation level. In the first cycle, Bukit Istana recorded the lowest value of background radiation which was -0.00244 mSv while Indera Mahkota 2 (IM2) recorded the highest background radiation with the value of 0.002038 mSv. For the last cycle, Indera Mahkota 15 (IM15) showed the highest reading of background radiation which was 0.016473 mSv whereas Indera Mahkota 8 (IM8) recorded the lowest value which was 0.010105 mSv. Conclusions: This study indicates that the background radiations in all seven residential areas near IIUM Kuantan Campus are within the recommended value for public exposure which is 1 mSv per year proposed by ICRP and IAEA.